2016
DOI: 10.1007/s12022-016-9455-2
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Ki-67 Determination in FNA Samples for Grading Pancreatic Neuroendocrine Tumors

Abstract: Neuroendocrine pancreatic tumors (PanNETs) are graded on the basis of their proliferative activity. Cytological samples are commonly the only samples available, but the determination of Ki-67 in cytology and its reliability as a measure of tumor mitotic activity is not well settled. We have retrospectively reviewed all the cases of FNA under EUS control of PanNETs in a 10-year period (2006-2016) in the Hospital Clínico San Carlos (Madrid). We identified 10 PanNET cases with histological correlation. Median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 32 publications
1
18
2
Order By: Relevance
“…12 PDX1 expression has been described before in the metastatic setting. 18 Furthermore, in contrast to ARX, PDX1 is expressed in pancreatic acinar and ductal cells ( Figure S1), and more abundantly in duodenum and islets of [19][20][21][22][23][24][25] It has been shown that accuracy decreases with larger tumors (with possible heterogeneity) and paucicellular cytologic specimens, but this was not seen in the current study. 21,24,26,27 The use of synaptophysin stained slides, annotated for areas with clusters of NET cells proved to be very useful and time saving in maximizing the cell count from cytologic specimens, without losing specificity (eg, lymphocytes or reactive tissue can have Ki67 positivity, and necrotic debris and blood often have nonspecific binding fluorescent foci which need to be manually check to be excluded).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…12 PDX1 expression has been described before in the metastatic setting. 18 Furthermore, in contrast to ARX, PDX1 is expressed in pancreatic acinar and ductal cells ( Figure S1), and more abundantly in duodenum and islets of [19][20][21][22][23][24][25] It has been shown that accuracy decreases with larger tumors (with possible heterogeneity) and paucicellular cytologic specimens, but this was not seen in the current study. 21,24,26,27 The use of synaptophysin stained slides, annotated for areas with clusters of NET cells proved to be very useful and time saving in maximizing the cell count from cytologic specimens, without losing specificity (eg, lymphocytes or reactive tissue can have Ki67 positivity, and necrotic debris and blood often have nonspecific binding fluorescent foci which need to be manually check to be excluded).…”
Section: Discussioncontrasting
confidence: 73%
“…This led to three grade 2 tumors to be erroneously classified as grade 1 tumors based on the Ki67 count in the cytologic specimen. Difficulties of correctly diagnosing intermediate grade or grade 2 PanNETs in cytology have often been reported and usually lead to an underestimation of grade . It has been shown that accuracy decreases with larger tumors (with possible heterogeneity) and paucicellular cytologic specimens, but this was not seen in the current study …”
Section: Discussioncontrasting
confidence: 70%
“…[ 17 ] In cytology samples, the Ki-67 PI index should be calculated in tumor hot spots. [ 11 , 18 ] In the present study, in the majority of cases ( n = 29), 500–2000 cell were counted for Ki-67 index except in three cases where only 200 cells could be counted. Weynand et al .…”
Section: Discussionmentioning
confidence: 63%
“…However, it is almost impossible to count in 50 HPFs with FNA samples, and the Ki-67 proliferation index is usually used in clinical practice. The concordance rate of the Ki-67 index between PNENs measured from EUS-FNA samples and surgical specimens was reported to be 54%-100% [37,[43][44][45][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] (Table 1), whereas a systematic review reported a rate of 83% [68]. Pooling the data of the studies which compared the Ki-67 LI grades obtained both in EUS-FNA samples and surgical specimen, the concordance rate was 77.5% and the kappa correlation index was 0.65 (95% confidence interval = 0.59 -0.71, P < 0.01) ( Table 2) [37,[43][44][45][49][50][51][52][54][55][56][57][58][59][60][61][62][63][64]…”
Section: Grading Diagnosismentioning
confidence: 99%
“…Table 2. Concordance of PNEN grading between EUS-FNAB specimens and surgical specimens in pooling data [37,[43][44][45][49][50][51][52][54][55][56][57][58][59][60][61][62][63][64][65][66]69]. Grade 1 Grade 2 Grade 3 Total Grade 1 338 88 5 431 Grade 2 32 111 12 155 Grade 3 0 0 23 23 Total 370 199 40 609…”
Section: Grading Diagnosismentioning
confidence: 99%